The Role of Ethnic Entrepreneurship and Personality on Business Sustainability in Barefoot Entrepreneurs in Wetlands: A Study on MSMEs Ethnic Madura - Anisah, Hastin Umi; Ikhwan Faisal; Akhmad Saupi Baihaki (HM Publisher, 2021)
Ethnic entrepreneurship is a set of connections and regular interaction patterns between people from the same background who migrate to carry out entrepreneurial activities in a certain region or country. This study aims to explore ethnic entrepreneurship in Banjarmasin. The results of this study explain that ethnic entrepreneurship and personality do not contribute significantly in increasing the sustainability of MSMEs in wetlands (Madurese ethnic traders). Entrepreneurship and personality do not contribute significantly in realizing business sustainability because ethnic entrepreneurship is an entrepreneurial mindset that is inherent in individual life